Association Between Fast Food–Related Media Exposure and Consumption Frequency Among Young Adults in Kepulauan Riau - Anggraini, Citra Dewi; Rizma, Amalina; Herviana, Herviana (Ikatan Sarjana Gizi Indonesia (ISAGI), 2026)
Overnutrition remains a major public health concern in Indonesia, with increasing prevalence among young adults. Fast food consumption, characterized by high fat and low nutrient content, has been associated with various behavioral and environmental determinants, including media exposure. This study aimed to analyze the association between fast food–related media exposure and consumption frequency among young adults. A cross-sectional study was conducted among 158 individuals aged 19–29 years in Kepulauan Riau, Indonesia, using purposive sampling. Data were collected through a structured electronic questionnaire assessing media exposure and frequency of fast food consumption. Statistical analysis was performed using Spearman’s rank correlation test. The results showed that the majority of respondents were highly influenced in fast food–related media exposure (68.4%) and reported frequently in fast food consumption frequency (51.9%). However, no significant correlation was found between media exposure and consumption frequency (p = 0.296), with a very weak positive correlation coefficient (r = 0.084). These findings suggest that media exposure alone is not a strong determinant of fast food consumption behavior. Other factors such as individual preferences, social influences, and environmental conditions may play a more substantial role. Future interventions should adopt a multifactorial approach by addressing not only media exposure but also individual, social, and environmental determinants of dietary behavior. Strengthening nutrition education and improving healthy food accessibility are essential to reduce fast food consumption among young adults.